Characterization of human, mouse and rabbit anti-gliadin antibodies by ELISA and western blotting - Vancíková, Z; Kocna, P; Tucková, L; Fric, P; Dvorák, M; Stoyanov, S; Tlaskalová-Hogenová, H (Folia microbiologica, 1995)
Monoclonal, hyperimmune rabbit and human serum anti-gliadin antibodies were analyzed by ELISA and immunoblotting techniques. In Western blotting the difference in reactivity between monoclonal and human antibodies was quantitative rather than qualitative. Rabbit antisera differed in reactivity according to the protein used for immunization. The rabbits immunized by the peptic-tryptic pancreatic digest of gliadin reacted similarly to the patients. In ELISA, significantly higher reactivity with crude, A-, glyc-gli, alpha-, beta- and omega-gliadins was found in the patients' sera than in controls.
Keywords: imunizace; Humans; Immune Sera; antisérum; Antibodies, Monoclonal; Blotting, Western; ELISA; lidé; zvířata; myši; Enzyme-Linked Immunosorbent Assay; Mice; gliadin; Gliadin; monoklonální protilátky; králíci; Animals; western blotting; Rabbits; Immunization